A Forward Contract sebagai Instrumen Manajemen Risiko dan Koordinasi Rantai Pasok dalam Agribisnis Peternakan: A Systematic Literature Review: Forward Contract sebagai Instrumen Manajemen Risiko dan Koordinasi Rantai Pasok dalam Agribisnis Peternakan - Sulthan Alam Syafa'at; Novie Andri Setianto; Yusmi Nur Wakhidi (UNIB Press, 2026)
Fluctuating prices and increasing supply chain complexity are major challenges in the development of livestock agribusiness. These conditions encourage the adoption of contract-based marketing mechanisms, particularly forward contracts, as efforts to manage risk and strengthen coordination among supply chain actors while increasing farmers’ income. This study aims to systematically examine the role of forward contracts in risk management and supply chain coordination in livestock agribusiness. The research method employed is a Systematic Literature Review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Scientific articles were collected from the Scopus, ScienceDirect, SpringerLink, Google Scholar, and Garuda databases using relevant keywords. Article selection was conducted based on inclusion and exclusion criteria applied to peer-reviewed journal publications published between 2014 and 2024. The selected articles were analyzed using a qualitative thematic synthesis approach. The findings indicate that forward contracts play a significant role in reducing price uncertainty, improving the stability of farmers’ income, and enhancing market access. In addition, forward contracts contribute to improved supply chain coordination through the strengthening of vertical relationships, supply certainty, and information exchange among business actors. However, the effectiveness of forward contracts is highly influenced by farmers’ bargaining power, institutional support, and contract design. This study concludes that forward contracts are a potential instrument for supporting the sustainability of livestock agribusiness, but they require appropriate regulation and facilitation to ensure that the benefits are distributed more equitably among livestock farmers.